2016
DOI: 10.1007/s11739-016-1581-9
|View full text |Cite|
|
Sign up to set email alerts
|

Usefulness of combining admission brain natriuretic peptide (BNP) plus hospital discharge bioelectrical impedance vector analysis (BIVA) in predicting 90 days cardiovascular mortality in patients with acute heart failure

Abstract: Heart failure is a disease characterized by high prevalence and mortality, and frequent rehospitalizations. The aim of this study is to investigate the prognostic power of combining brain natriuretic peptide (BNP) and congestion status detected by bioelectrical impedance vector analysis (BIVA) in acute heart failure patients. This is an observational, prospective, and a multicentre study. BNP assessment was measured upon hospital arrival, while BIVA analysis was obtained at the time of discharge. Cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
0
20
0
4
Order By: Relevance
“…Similarly, it has been recently reported that plasma volume status, calculated by means of Duarte's formula, correlates with adverse prognosis in patients with AHF [5,[17][18][19]. All of these parameters seemed to be independent predictors of poor prognosis in HF patients, independent of BNP values [5,10,12,13,18].…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Similarly, it has been recently reported that plasma volume status, calculated by means of Duarte's formula, correlates with adverse prognosis in patients with AHF [5,[17][18][19]. All of these parameters seemed to be independent predictors of poor prognosis in HF patients, independent of BNP values [5,10,12,13,18].…”
Section: Introductionmentioning
confidence: 61%
“…interstitial fluid status), which confirmed its prognostic role in our study. The literature has indicated that HI is a good 90-day (C-Index: 0.71) [10] and 1-year (C-Index: 0.72) [9] predictor of mortality in patients with AHF. Our findings confirmed the good diagnostic performance of this marker in predicting long-term mortality (C-Index 0.72) and identified a cut-off value of 73.8% (close to 74.3%, as reported by Núñez et al [11]).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…However, as long as congestion has been adequately treated, these increases are not associated with a worse prognosis. 13 , 14 In our experience, creatinine, in these cases, usually falls at the end of hospitalization or about 30 days after discharge. 14 , 15 In other words, elevated creatinine at admission appears to be a reflection of congestion of the renal veins and transient increases are a consequence of the volume reduction process.…”
Section: Hypotension Bradycardia and Renal Dysfunction As Obstacles mentioning
confidence: 69%
“…Congestion, regardless of worsening of renal function, is associated with worse prognosis. 14 , 16 The intense and persistent increase in creatinine seems to indicate a worse prognosis, but transient increases do not. 16 Therefore, the diuretic and the ACEI should be maintained in this situation, in which there are still evident signs of congestion, despite the increase of slag.…”
Section: Hypotension Bradycardia and Renal Dysfunction As Obstacles mentioning
confidence: 99%